COMPARATIVE ANALYSIS OF EFFLUENT FROM VARIOUS STP’s WITH CPCB STANDARD IN GREATERNOIDA REGION - Choudhary, Adesh; Yasin, Mohd Ayub (International Journal of Psychosocial Rehabilitation, 2020)
Sewage treatment plays a vital role before disposing of the wastewater directly into a river or land. Therefore, proper sewage treatment should be given to wastewater or sewage. The need to perform this study is to examine whether the effluent from the sewage treatment plant complies with the general standard of the central Pollution control board. In this study samples are collected from the vent of the conduct stand and analyses the devastate of water superiority parameter. The conclusions draw from this study will determine the sewage discharge is under the acceptable limit followed by cpcb